Relationship of caregivers' schizophrenia literacy and frequency of readmission of their patients with schizophrenia at the national center for mental health: a prospective cohort study - Bajador, Jerico H.
Background: Mental health literacy (MHL) pertain to "knowledge and beliefs about mental disorders which aid their recognition, management and prevention." There were several studies on MHL, but very few when it was applied to a specific mental disorder such as schizophrenia. This study aimed to determine if there is a relationship between caregivers' schizophrenia literacy (SL) and frequency of readmission of their patients with schizophrenia.